Negative Indefinite Constructions in Bantu: ‘Nobody’ - Maud Devos; Johan van der Auwera; Rasmus Bernander (Languages, 2025)
This paper presents a first typology of negative indefinites in Bantu languages. The lack of interest in expressions of ‘nobody’ in Bantu languages is connected with the idea that they merely involve a generic noun for ‘person’ and main clause negation. Our study, based on a dataset of 85 Bantu languages, shows that exponents of ‘nobody’ can be quite diverse, either resembling exponents of ‘somebody’ or differing from them through the use of pragmatically strong modifiers like scalar additive operators or explicit quantifiers like the numeral ‘one’. We also look at the constructions in which exponents of ‘nobody’ occur and observe that next to canonical SVO constructions, two construction types are used which are known to express information structure in Bantu languages: inversion constructions and existential cleft constructions. Inversion constructions are shown to be especially frequent with intransitive clauses but we also find object inversion for either ‘somebody’ or ‘nobody’ but not for both in the same language. Existential cleft constructions, on the other hand, are shown to be especially frequent with transitive clauses and, more importantly, they are more frequently used for expressions of ‘nobody’ than for expressions of ‘somebody’ in line with recent observations for South-East Asian and Mixtec languages.